DEVELOPING 21St CENTURY SKILLS TROUGH WRITING CLASS IN ENGLISH LANGUAGE EDUCATION DEPARTMENT - Nugraha, Irfan Setia; Putra, Fahry Rizaldy (Institut of Shanti Bhuana, 2023)
Due to the improvement in technologies, the era of industry 4.0 was born (Ghobakhloo, 2020) mentions that the era of industry 4.0 contribute to the sustainability of the economy, environment, and social development whilst gaining the attention of the world. The purpose of this study is to explore some aspects of creative writing that can develop 21st-century skills for students. This research used the definition of 21st century skills initiated by (National Research Council, 2011) as the key finding of the research which have 3 cluster of skills Cognitive skills, Interpersonal skills and Intrapersonal skills. The elaboration of making a text based on the situation or a picture does need an ability to think critically, making question of the picture or the situation is one of the steps shown in the research and it require the skills of critical thinking. To sum up, the 21st century skills is urgently needed to prepares students in near future to help them survive the working environment. By analysing activities in creative writing using the definition of 21st century skills by (National Research Council, 2011) the author could say that 21st century skills can be developed through writing class